META ANALISIS PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA - Safa Sabela; Lessa Roesdiana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Until now, research on the application of guided inquiry learning models to students understanding of mathematical concepts has been carried out with varying finding. Therefore, a meta analysis study was conducted to verify the overall effect of the guided inquiry learning model on students understanding of mathematical concepts. By investigating Google dan Google Scholar databases and using predetermined keywords, 13 scientific papers were obtained. Of the 13 scientific papers, based on the inclusion criteria, 10 scientific papers were worthy of analysis. The analysis of scientific papers was carried out using the effect size index from the Hedges’g equation and the JASP software using a fixed effects model to determine the overall effect size estimate. The results obtained that the overall effect size from the application of the guided inquiry learning model to students understanding of mathematical consepts is 0,645 with a standard error of 0,084 and it is proven that this research is not indicated by publication bias. Thus, this study indicates that the application of the guided inquiry learning model is quite effective in improving students understanding of mathematical concepts because it has a fairly high positive effect.